Factibilidad para la creación de una empresa dedicada al diseño, planificación y construcción de redes eléctricas en baja, media y alta tensión para las constructoras de la ciudad de Quito - Carrera León, Luis Aníbal (2016)
Electricity plays a vital role in the daily routine of people and this is reflected in covering their use, both in scientific, cultural, technological, medical, well, you could say that without electricity today, the world does not move and that we owe it to all scientists throughout history tried to find him and today have baptized with names the theories used today. With this we want to reach, with a changing and growing world population looking for a home, whether home or apartment, which hold their belongings, and it must be equipped with electricity, so this project is aimed the development of electrical design projects low, medium and high voltage for residential construction in the city of Quito. Initially it was taken as reference for market research to construction activity and that are based in the City of Quito, taking a survey to 151 companies for a 100% effectiveness. For the project development methods such as inductive, deductive, analytical and mathematical, also techniques of direct observation, document collection and literature survey or interview were used. With market research, demand and supply could be determined there is an unmet demand for year 1633, which represents only 8.82% coverage of demand. The size and capacity of the company would cover the coverage and without any inconvenience to cover increased demand projection installed, of course the increasing human resources to cover that increase. Projected to begin investing activities is $ 21,900.42 US dollars of the United States of NA, which will be funded in part by the shareholders 70% and the rest by a 30% loan to BNF. The both administrative and operational human talent conform a total of seven people. In the analysis of the financial evaluation it was determined that the NPV is $ 56,638.89, which is greater than one, so that the project is viable implementation. The capital recovery period would be 1 year 1 month 19 days. And for every dollar invested would be profit taking as 0.51 cents, so in short the project is totally viable. Finally, conclusions and recommendations of the case are presented, which should be considered and taken into account for professionals or entrepreneurs and wish to refer this study to implement future. .